Triple bulk heterojunctions as means for recovering the microstructure of photoactive layers in organic solar cell devices - Kan, Zhipeng; Colella, Letizia; Canesi, Eleonora V.; Lerario, Giovanni; Kumar, R. Sai Santosh; Bonometti, Valentina; Mussini, Patrizia R.; Cavallo, Gabriella; Terraneo, Giancarlo; Pattanasattayavong, Pichaya; Anthopoulos, Thomas D.; Bertarelli, Chiara; et al. (My University, 2014)
Herein we present a methodology for improving the power conversion efficiency of organic solar cells made by photoactive layers of poly(3-hexylthiophene) (P3HT) and phenyl-C61 butyric acid methyl ester (PCBM) of non-optimized microstructure. In our study we achieve a 47% improvement in the power conversion efficiency (PCE) of the device by utilizing a thiophene-based quinoid (QBT) moiety as the third component in the P3HT:PCBM:QBT photoactive layers. Based on a set of independent characterization experiments we address the QBT composition dependent photophysical, electrical, thermal, structural and morphology-related properties of the ternary photovoltaic P3HT:PCBM:QBT system for elucidating the origin of the PCE improvement. In small amounts (0.3-0.6 wt%), QBT serves as a nucleation agent, it enlarges the size of the P3HT crystallites by 15% and it increases the fraction of well-ordered P3HT chains in the P3HT:PCBM:QBT layer. The improved microstructure of the photoactive layer in combination with the QBT-assisted photo-induced hole transfer step from PCBM to P3HT, lead to an increase of the charge photogeneration yield in the P3HT:PCBM:QBT triple bulk heterojunction. The relatively small optical gap of QBT facilitates a resonant energy transfer step from the photoexcited PCBM to the QBT followed by a charge transfer process between QBT and the P3HT matrix. Based on these findings we propose general guidelines for the design of next generation functional additives to be used in organic photovoltaics. © 2013 Elsevier B.V.
Keywords: Additives; n-Type acceptors; Organic photovoltaics; Photon harvesting; Quinoid; Ternary blend